2012
DOI: 10.1111/j.1477-2574.2012.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to comply with NCCN guidelines for the management of pancreatic cancer compromises outcomes

Abstract: There is relatively poor overall compliance with the NCCN PC guidelines in California's large hospitals. Higher compliance rates are correlated with improved survival. Compliance is an important potential measure of the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 37 publications
3
99
1
2
Order By: Relevance
“…This may be, in part, because patients with low SES tend to receive suboptimal care that deviates from established guidelines (15,16). Underprivileged patients are also less likely to comply with cancer screening recommendations (2) and prescribed systemic treatments (3).…”
Section: Discussionmentioning
confidence: 99%
“…This may be, in part, because patients with low SES tend to receive suboptimal care that deviates from established guidelines (15,16). Underprivileged patients are also less likely to comply with cancer screening recommendations (2) and prescribed systemic treatments (3).…”
Section: Discussionmentioning
confidence: 99%
“…16,29,30 Adherence to established guidance for cancer management can have a positive effect on quality of care, and compliance with NCCN guidelines has been shown to improve survival by > 30%. 16,31 Altogether, a complete baseline diagnostic work-up is essential to optimize the treatment plan and monitor response in NDMM patients. In an era in which the implementation of electronic medical records is evolving, inclusion of NCCN mandated fields would help drive their use.…”
Section: Discussionmentioning
confidence: 99%
“…While these guidelines are extensive and beyond the scope of this review, compliance with these guidelines has been demonstrated to convey a survival advantage compared to noncompliant care. This survival benefit persists even in high volume settings (Visser et al, 2012). In addition to suggesting care algorithms, these guidelines suggest patients should receive care at a high volume center under the direction of a multidisciplinary committee.…”
Section: Standards Of Care-an Overviewmentioning
confidence: 98%